Características clínico-epidemiológicas y de laboratorio asociadas a falla renal aguda en pacientes con diagnóstico de dengue hospitalizados en el servicio de medicina del Hospital Iquitos, enero-abril 2022 - Romayna Piña, Margiori Celeste (2022)
Acute renal failure is one of the least studied complications of dengue, it is a disorder that affects people all over the world and has a high morbidity and mortality. Therefore, the purpose of this study is to determine the clinical-epidemiological and laboratory characteristics associated with acute renal failure in patients diagnosed with dengue hospitalized in the medical service of the Iquitos Hospital, January-April 2022. A sample of 68 patients was taken. Concluding that 19.1% of the patients presented acute renal failure. It was determined that patients with dengue who presented a hospital stay greater than or equal to 4 days (p<0.004), rash (p=0.014), and leukocytes less than 4000 cells/mm3 (p=0.028) presented a statistically significant association with acute renal failure.